Blood pharming: exploring the progress and hurdles in producing in-vitro red blood cells for therapeutic applications - Hassan, Hammad; Rajput, Sheerien (Frontiers in Hematology, 2024)
Transfusion Medicine is facing mounting challenges, including but not limited to donor availability, blood supply shortages, and transfusion-associated complications, such as immunogenicity and transmission of viral infections. ‘Blood Pharming’, for in vitro Red Blood Cells (RBC) synthesis, offers a potentially effective approach to addressing the challenges and risks associated with the transfusion of blood and related products. This innovative approach employs cells from variable sources such as Hematopoietic stem cells (HSCs), induced pluripotent stem cells (iPSCs), or immortalized progenitor cell lines, directing their differentiation towards erythropoiesis in an in-vitro environment that mimics the normal bone marrow niche required for erythropoiesis. This review article provides a comprehensive analysis of the progress and hurdles in blood pharming, emphasizing in vitro RBC synthesis for clinical application. In-vitro large-scale production of RBCs offers cutting-edge advantages, such as consistent scalability, the capacity to acquire desired blood phenotypes, and a significant reduction in transfusion-related infections, however, substantial molecular and methodological challenges still need to be addressed before the transfer of this approach from bench to bedside. The review discusses the challenges in ensuring scalability that matches demand and supply, the structural and functional integrity of in-vitro synthesized RBCs compared to their in-vivo counterparts, and the cost-effective methods of RBC synthesis in vitro. It also highlights the importance of implementing thorough characterization and testing protocols to comply with regulatory standards. Additionally, it delves into the ethical concerns associated with commercializing such products. In summary, this review examines the progress and obstacles in the field of in-vitro blood pharming. Through a comprehensive analysis of the present state of the discipline, ongoing scholarly investigations, and prospective avenues of inquiry, our objective is to contribute to a more profound comprehension of the potential impact of synthetic RBCs on the transformation of transfusion medicine.